A Fast and Efficient Approach to Obtaining High-Purity Glioma Stem Cell Culture - Han, Xin-Xin; Cai, Chunhui; Yu, Li-Ming; Wang, Min; Hu, Dai-Yu; Ren, Jie; Zhang, Meng-Han; Zhu, Lu-Ying; Zhang, Wei-Hua; Huang, Wei; He, Hua; Gao, Zhengliang (Frontiers in Genetics, 2021)
Glioma is the most common and malignant primary brain tumor. Patients with malignant glioma usually have poor prognosis due to drug resistance and disease relapse. Cancer stem cells contribute to glioma initiation, progression, resistance and relapse. Hence, quick identification and efficient understanding of glioma stem cells is of profound importance for therapeutic strategies and outcomes. Ideally, therapeutic approaches will only kill cancer stem cells without harming normal neural stem cells that can inhibit glioma stem cells and are often beneficial. It is key to identify the differences between cancer stem cells and normal neural stem cells. However, reports detailing an efficient and uniform protocol are scarce, as are comparisons between normal neural and cancer stem cells. Here, we compared different protocols and developed a fast and efficient approach to obtaining high-purity glioma stem cells by tracking observation and optimizing culture conditions. We examined the proliferative and differentiative properties confirming the identities of the GSCs with relevant markers such as Ki67, SRY-box containing gene 2 (Sox2), an intermediate filament protein member Nestin, glial fibrillary acidic protein (GFAP) and s100 calcium-binding protein (s100-beta). Finally, we identified distinct expression differences between glioma stem cells and normal neural stem cells including cyclin dependent kinase 4 (Cdk4) and tumor protein p53 (TP53). This study comprehensively describes the features of glioma stem cells, their properties, and regulatory genes with expression differences between them and normal stem cells. Effective approaches to quickly obtaining high-quality glioma stem cells from patients should have the potential to not only help understand the diseases and the resistances but also enable target drug screening and personalized medicine for brain tumor treatment.